Violent Conflict and Forced Displacement in the Horn of Africa: Government and Donor Policies and Programs in Search of Durable Solutions (African Human Mobility Review, 2021)
The Horn of Africa (HOA) is currently engulfed in entangling and shifting cross border conflict, resulting in at least four major forced displacement situations. These conflicts emanate mainly from the Sudan, South Sudan, Somalia and Eritrea and involve large numbers of refugees as well as internally displaced persons (IDPs). Globally, there are an estimated 54.7 million displaced persons. More than a quarter (27%) of the globally displaced, are in Sub-Saharan Africa, with about 8.7 million or over half (58%) of those in the HOA.On the one hand, forced displacement in the Horn places additional stresses on already weak local and national institutions and marginalized, underserved host communities. Services are often perceived to only benefit the displaced as opposed to receptor communities leading to envy and local conflict. On the other hand, displaced persons also have skills and assets that could be harnessed and utilized to benefit the local economy in pursuit of durable solutions. The complex cultural, social, and political nature of the region is compounded by an ongoing set of development challenges, including: demographic shifts; imbalanced service provision; the threat of pandemic diseases; and increasing contestation over scarce natural resources, especially water and grazing areas.This article examines the underlying drivers of violent conflict, the impact on both the displaced and the receptor host communities, and the effectiveness of government and donor policies and programs. The research methodology included a literature review, field-based participant observations, and a series of in-depth key informant and focal group interviews in HOA refugee camps, host communities and major cities.The search for a new paradigm shift from care and maintenance to resilience and self-reliance is underway. Given the now â€œprotractedâ€ nature of the displacement, the old encampment humanitarian approaches of care and maintenance are now giving way to a rethink from a development perspective by governments and donors alike.Finally, from a prevention perspective, stemming forced migration at its source by improving security, governance, and livelihood opportunities in countries of origin are key to managing the displacement challenge. Regional integrated area development can convert fragile border areas which now serve as shock absorbers for conflicts within these fragile states to prosperous change agents opening avenues of cross border trade and development.